Physiotherapy interventions in post- and long-COVID-19: a scoping review protocol - Gartmann, Judith; Sturm, Christian; Boekel, Andrea (BMJ open, 2024)
IntroductionPost- or long-COVID-19 conditions manifest with a spectrum of symptoms reminiscent of pulmonary, musculoskeletal, psychological and neurological disorders. Individuals with post- or long-COVID-19 syndrome often present with myalgia, pulmonary problems and fatigue, which significantly impact their daily functioning. Physiotherapy interventions are an accepted medical remedy for these symptoms. This scoping review aims to outline the evidence of physiotherapy interventions documented in the scientific literature, specifically focusing on hands-on therapy.Methods and analysisThis scoping review conforms to the methodological framework established by the Joanna Briggs Institute (JBI). The procedure for drafting a scoping review involves several steps, starting with defining the research question and the inclusion and exclusion criteria. Eligible studies are those analysing physiotherapy treatment parameters for direct patient interaction in post- and long-COVID-19 patients. Telemedicine and entirely home-based workouts will be excluded aligning with the context of outpatient physiotherapy in Germany. The literature search will be conducted in PubMed, EBSCO research, Scopus, Web of Science, Embase, PEDRO, Cochrane and WISO databases by two independent researchers. Screening, data extraction and a critical appraisal will be performed by these researchers using assessment tools provided by the JBI. Extracted data will encompass demographic characteristics, definitions of post- or long-COVID-19 conditions, descriptions of interventions, their treatment parameters and treatment outcome. Subsequently, findings will be disseminated through a scoping review article or conference presentation.Ethics and disseminationGiven that this review does not involve human participants, ethical committee approval is deemed unnecessary. The results will be published in peer-reviewed journals and presented at academic and physiotherapeutic conferences.